Keadilan Restoratif: Upaya Menemukan Keadilan Substantif? - Wahid, Abdul (Jurnal Ius Constituendum, 2022)
Substantive justice is an idea of justice that seeks to present it comprehensively and completely in society. Substantive justice in this case does not only interpret the law as limited to rules and procedures, but also interprets the law more holistically, including the value of justice in society. In the criminal justice system, the presence of restorative justice is one of the efforts to realize substantive justice. This study aims to explore aspects of restorative justice as an effort to realize substantive justice as a new development in the idea of a state of law and justice. The approach used in this research is a legislative approach, a conceptual approach, and a philosophical approach related to philosophical aspects. The results of the study confirm that the essence of restorative justice is a balanced relationship between the interests and harmonization of the community, perpetrators, and victims simultaneously. In addition, after the aspect of community harmonization is fulfilled, restorative justice seeks to implement a proportional relational relationship between the victim and the perpetrator. The application of substantive justice through restorative justice in the context of legal discovery, namely the presence of the inclusion of restorative justice in Book I of the Draft Criminal Code can be used as an orientation and legal method for legal apparatus in the criminal justice system through anticipatory interpretation and teleological interpretation. The recommendation offered in this study is the need for the application and practice of restorative justice through further regulation and implementation in each law enforcement institution to optimize the restorative justice-based criminal justice system.Keadilan substantif merupakan gagasan keadilan yang berupaya menghadirkan secara komprehensif dan paripurna di masyarakat. Keadilan substantif dalam hal ini tidak hanya memaknai hukum sebatas aturan dan prosedur, tetapi memaknai hukum secara lebih holistik termasuk nilai keadilan di masyarakat. Dalam sistem peradilan pidana hadirnya restorative justice merupakan salah satu upaya untuk mewujudkan keadilan substantif. Penelitian ini bertujuan menggali aspek restorative justice sebagai upaya untuk mewujudkan keadilan substantif sebagai perkembangan baru dalam gagasan negara hukum dan keadilan. Penelitian ini merupakan penelitian hukum normatif yang berorientasi pada pengkajian gagasan keadilan substantif dan konsep restorative justice. Hasil penelitian menegaskan esensi dari restorative justice adalah relasi yang seimbang antara kepentingan dan harmonisasi masyarakat, pelaku, dan korban secara simultan. Selain itu, setelah aspek harmonisasi masyarakat terpenuhi maka restorative justice berupaya menerapkan hubungan relasional yang proporsional antara korban dan pelaku. Penerapan keadilan susbtantif melalui restorative justice konteks penemuan hukum yaitu dengan hadirnya pencantuman restorative justice dalam Buku I Rancangan Undang-Undang KUHP dapat dijadikan sebagai orientasi serta cara berhukum bagi aparatur hukum dalam sistem peradilan pidana melalui interpretasi antisipatif dan interpretasi teleologis. Rekomendasi penelitian ini adalah perlunya penerapan dan praktik restorative justice melalui adanya pengaturan dan pelaksanaan lebih lanjut di masing-masing institusi penegak hukum untuk mengoptimalkan sistem peradilan pidana berbasis restorative justice.